The long decade: how 9/11 changed the law - Jenkins, David; Jacobsen, Amanda; Henriksen, Anders (Oxford University Press, 2014)
This collection contains contributions by international legal scholars who critically reflect on how the terrorist attacks of 9/11 precipitated the reactionary legal changes, and examines how the uncertainties of the 'long decade' made fear a political and legal force, challenged national constitutional orders, altered fundamental assumptions about the rule of law, and ultimately raised questions about how democracy and human rights can cope with competing security pressures, while considering the complex process of crafting anti-terrorism measures.